DETERMINATION OF ANTICYCLOOXYGENASE COMPONENT IN THE MECHANISM OF ANTI-EXUDATIVE EFFECT OF BENFURAM - Корнієнко, В.І. (World of Medicine and Biology, 2018)
The inflammatory process is a widespread symptom of most diseases in humans. Non-steroidal anti-inflammatory drugs (NSAIDs) on the principle of their effect on the activity of COX are subdivided into the non-selective inhibitors capable of blocking COX-1 and COX-2, and the selective ones predominantly suppressing the activity of COX-2. It is at the expense of the COX-2 blockade NSAIDs express their anti-inflammatory, analgesic and antipyretic effects, whereas the blockade of COX-1 activity leads to inhibition of the PG protective action and the development of undesirable side effects. The purpose of the research was to study the anti-cyclooxygenase component in the mechanism of benfuram action. The activity of the COX-1 isoenzyme was highest in the blood serum (0.354 ± 0.021 nmol/min/ml), it was observed lower in the gastric mucosa (0.283 ± 0.024 nmol/min/ml) and still lower in the brain (0.234 ± 0.018 nmol/min/ml). In rats of the second group with experimental acute carrageenan inflammation of the paw, the activity of the COX-1 isoenzyme in the blood serum increased by 1.63 times, in the mucous membrane of the stomach by 1.75 times, and in the brain by 1.97 times compared with the first intact group. Application of benfuraam as an anti-inflammatory agent in rats with experimental carrageenan edema of the paw showed less activation of the COX-1 isoenzyme. Thus, in the blood serum, the COX-1 activity decreased by 31.7%, in the mucous membrane of the stomach by 35.3%, and in the brain by 39.8% in comparison with the experimental carrageenan edema in the control group rats. Diclofenac sodium reduced the activity of the COX-1 isoenzyme in comparison with the control group and its effect on COX-1 can be compared with the anti-inflammatory effect of benfuram.The studied drugs in various ways blocked the COX-1 and COX-2 isoenzymes initiation. Benfuram and diclofenac sodium reduced the expression of the COX-2 isoenzyme, proving its expressed anti-inflammatory properties. The most significant COX-2 inhibition was caused by benfuram. In the development of experimental inflammation, benfuram retained the activity of this isoenzyme within the intact control group. At the same time, benfuram practically did not affect the activity of COX-1 and did not interfere with the work of the compensatory protection mechanisms. Comparison of the drug’s inhibitory activity in the ratio COX-2 to COX-1 permits to assess its potential toxicity.The risk of developing severe complications is significantly higher on treatment with drugs that have low selectivity for COX-2. The greater the value in the ratio of the COX-1 inhibition activity compared with that of COX-2, the more effective the drug is for COX-2 and, therefore, it is less toxic.Thus, significant inhibition of COX-2 isoenzyme was caused by benfuram, which provided anti-inflammatory action, did not affect the COX-1 activity and did not interfere with the work of compensatory protection mechanisms in the mucous membranes of the stomach and duodenum.
Keywords: benfuram; antiexudative activity; isoenzymes of COG-1 and COG- 2